Estimation Risk, Information, and the Conditional CAPM: Theory and Evidence - Kumar, Praveen; Sorescu, Sorin M.; Boehme, Rodney D.; Danielsen, Bartley R. (Review of Financial Studies, 2008)
We theoretically and empirically investigate the role of information on the cross section of stock returns and firms' cost of capital when investors face estimation risk and learn from noisy signals of uncertain quality. The resultant equilibrium is an information-dependent conditional CAPM. We find strong empirical support for the model. Innovations in market volatility, oil prices, exchange rates, and dispersion of analysts' forecasts not only help explain the cross section of stock returns, but their influence depends on the stock's systematic estimation risk. Moreover, dividend and share repurchase initiations have significant downward announcement effects on estimated betas and their standard errors.